Challenges and limitations in using bacterial metabolites as immunomodulators - Chinnashanmugam Saravanan; Nandana Karrath Gopinath; Raja Ganesan; Durairaj Thirumurugan (Frontiers in Cellular and Infection Microbiology)
Harnessing the immunomodulatory potential of bacterial metabolites opens up exciting possibilities for treating various immune-related disorders. However, turning this potential into a reality presents significant challenges. This review investigates these challenges, focusing on discovery, production, characterization, stability, formulation, safety, and individual variability limitations. The limited bioavailability of many metabolites, as well as potential improvements along with the potential for off-target effects and the importance of precise targeting, are emphasized. Furthermore, the complex interactions between gut bacterial metabolites and the microbiome are investigated, highlighting the importance of personalized approaches. We conclude by discussing promising advances in metagenomics, metabolomics, synthetic biology, and targeted delivery systems, which hold out hope for overcoming these limitations and paving the way for the clinical translation of bacterial metabolites as effective immunomodulators.